PEMBERLAKUAN BALANCE SCORECARD UNTUK MENGUKUR KINERJA PELAYANAN DI KEBUN BINATANG KOTA SURABAYA INDONESIA - Septi Rahayu (Akuntansi, 2022)
Surabaya Zoo which was founded in 1916 experienced the effects of globalization in which the change occur very rapidly. Customer wants and needs (tourists) are constantly changing, science and technology that continues togrow and compatition among businesses pariwisaata an increasingly sharp, forcing the Surabaya Zoo to constantly improve its ability to provide travel services. The purposeof this study is to analyzee in depth how the implementation of the concept of balance scorecard to measure performance of the Surabaya Zoo. The concept of balance scorecard at the Surabaya Zoo includes four persepectives and the persepectives of four each-each have several strategic targets, performance measure and targets to be achieved. The four persepectives are : (1) Financial Persepective targeting strategy : increased surpluses, increased revenue, and cost reduction, performance measure used is the percentage increase in surplus, the precentage change in revenue and decrease costs. (2) Customer Persepective targeting strategies : the speed of service, quality relationship with the customer, the performance measure used is the throughput time, customer retention. (3) Internal Business Process Persepective with strategic objectives : incerased development and product marketing, performance measure used are service error rate, comparisons of the old infrastructure with new ones, the precentage of revenue from new products. (4) Learning and Growth Persepective with strategic objectives : increased employee productivity, increased commitment of personnal, the performance measure used is the percentage of employees who educated and trained, personnal satisfaction.